Desenvolvimento de nódulos em Sesbania virgata e a importância dos exopolissacarídeos em sua simbiose com Azorhizobium doebereinerae - Bomfeti, Cleide Aparecida (2010)
Sesbania virgata is a tropical pioneer legume which occurs naturally in Brazil and is used for the regeneration of degraded soils and reforestation of gallery forests. S. virgata only develops an efficient symbiosis when inoculated with strains of Azorhizobium doebereinerae. The other species of the genus Azorhizobium, A. caulinodans, has phenotypic and genotypic similarities with A. doebereinerae and establishes an efficient symbiosis when inoculated in S. rostrata, which is native to Africa. However, despite the similarity between A. caulinodans and A. doebereinerae, A. caulinodans forms pseudonodules in S. virgata and A. doebereinerae forms ineffective nodules in S. rostrata. In this work, we characterized the root nodule morphogenesis of S. virgata through light, fluorescence and transmission electronic microscopy. In addition, to investigate bacterial genetics aspects of this nodulation process, approximately 2000 mutants were generated by Tn5 insertions. As observed in S. rostrata, the root nodulation of S. virgata under flooded conditions occurs via cracks (crack entry). The development of the infected tissue involves the formation of infection threads and the establishment of an apical meristem resulting in indeterminate nodules. However, compared to S. rostrata, the complete fixation zone differentiation in S. virgata shows a slower development. Using our bacterial mutant library, two exopolysaccharides mutants were selected on YEB agar containing 0,01% Congo Red. The characterization of these mutants show the formation of rough pink colonies, with subsequently darkening at the center, giving a "bulls eye" appearance. Once inoculated in S. virgata, these mutants produced smaller and paler nodules only after 21 days of inoculation and the host plant showed features of nitrogen starvation demonstrating the importance of EPS in the symbiosis stabilisment.